2014
DOI: 10.5312/wjo.v5.i4.412
|View full text |Cite
|
Sign up to set email alerts
|

Current concept in dysplastic hip arthroplasty: Techniques for acetabular and femoral reconstruction

Abstract: Adult patients with developmental dysplasia of the hip develop secondary osteoarthritis and eventually end up with total hip arthroplasty (THA) at younger age. Because of altered anatomy of dysplastic hips, THA in these patients represents technically demanding procedure. Distorted anatomy of the acetabulum and proximal femur together with conjoined leg length discrepancy present major challenges during performing THA in patients with developmental dysplasia of the hip. In addition, most patients are at younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 69 publications
0
49
0
11
Order By: Relevance
“…Various techniques using different anatomic levels and cutting shapes have been described. Anatomic levels are greater trochanter, subtrochanteric region of the proximal femoral metaphysis, and distal femur [10][11][12]. Subtrochanteric osteotomies can be performed as transverse, oblique, Z-shaped, or double Chevron [7,8,[13][14][15][16].…”
mentioning
confidence: 99%
“…Various techniques using different anatomic levels and cutting shapes have been described. Anatomic levels are greater trochanter, subtrochanteric region of the proximal femoral metaphysis, and distal femur [10][11][12]. Subtrochanteric osteotomies can be performed as transverse, oblique, Z-shaped, or double Chevron [7,8,[13][14][15][16].…”
mentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) encompasses a spectrum of altered hip anatomy that often consists of an underdeveloped acetabulum, uncovered or dislocated femoral head, and acetabular retroversion [1]. Furthermore, additional deformities include a dysplastic femur with increased anteversion, a shorter femoral neck, and an elliptic femoral head [1]. These structures and subsequent altered biomechanics are thought to contribute to accelerated degeneration of the dysplastic hip joint [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional deformities include a dysplastic femur with increased anteversion, a shorter femoral neck, and an elliptic femoral head [1]. These structures and subsequent altered biomechanics are thought to contribute to accelerated degeneration of the dysplastic hip joint [1,2]. A subset of these patients ultimately requires total hip arthroplasty (THA) due to the long-term sequelae of untreated DDH.…”
Section: Introductionmentioning
confidence: 99%
“…Koulouvaris et al reported in 2008 an interesting combined procedure where distal femoral shortening procedure was performed as an addition to THR of dysplastic and difficult-to-reduce hips. 48,49 One of the major advantages of this technique is the possibility of combined correction of the ipsilateral knee valgus deformity, which can be performed simply by changing the shape of resection fragment.…”
Section: Femoral Reconstructionmentioning
confidence: 99%